Chemical bonding in cuprous complexes with simple nitriles: octet rule and resonance concepts versus quantitative charge-redistribution analysis. Issue 36 (25th June 2020) - Potenti, Simone; Paoloni, Lorenzo; Nandi, Surajit; Fusè, Marco; Barone, Vincenzo; Rampino, Sergio
Abstract : Resonance structures for six cuprous complexes with simple nitriles are interpreted by means of a quantitative analysis of charge redistribution upon copper-nitrile bonding. Abstract : Chemical bonding in a set of six cuprous complexes with simple nitriles (CN −, HNC, HCN, CH3 NC, and CH3 CN) is investigated by means of a recently devised analysis scheme framed in density-functional theory and quantitatively singling out concurrent charge flows such as σ donation and π backdonation. The results of our analysis are comparatively assessed against qualitative models for charge redistribution based on the popular concepts of octet rule and resonance structures, and the relative importance of different charge-flow channels relating to σ donation, π back-donation, polarization, and hyperconjugation is discussed on a quantitative basis.